2021
DOI: 10.1007/s12613-020-2121-1
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening mechanisms of reduced activation ferritic/martensitic steels: A review

Abstract: This review summarizes the strengthening mechanisms of reduced activation ferritic/martensitic (RAFM) steels. High-angle grain boundaries, subgrain boundaries, nano-sized M 23 C 6 , and MX carbide precipitates effectively hinder dislocation motion and increase high-temperature strength. M 23 C 6 carbides are easily coarsened under high temperatures, thereby weakening their ability to block dislocations. Creep properties are improved through the reduction of M 23 C 6 carbides. Thus, the loss of strength must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 118 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, there have been preliminary studies on the hot deformation behavior of RAFM cladding tubes. [22][23][24] Fang et al [25] studied the effect of strain rates on the hot deformation and dynamic recrystallization (DRX) in China low-activation martensitic (CLAM) steel. The researchers found that DRX more easily occurs with high strain rates under large deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there have been preliminary studies on the hot deformation behavior of RAFM cladding tubes. [22][23][24] Fang et al [25] studied the effect of strain rates on the hot deformation and dynamic recrystallization (DRX) in China low-activation martensitic (CLAM) steel. The researchers found that DRX more easily occurs with high strain rates under large deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to balance the impact toughness and wear resistance in order to improve the service life of the tools [25][26][27]. Generally speaking, there are many methods to improve the contradictory mechanical properties of steel, such as ultra-pure purification, heat treatment, large forging ratio and so on [21,[28][29][30][31]. However, on a technical level, the tool and die steel for cutting tools has reached a certain limit.…”
Section: Introductionmentioning
confidence: 99%
“…Creep performance is a critical criterion for evaluating durability at elevated temperatures and stresses, which directly determines the development cycle of high-performance heat-resistant alloys. [1][2][3][4][5][6] For commercial martensitic heat-resistant steels, such as grade 91, grade 92, grade 122, etc., the creep performance is one of the remarkable properties required to be provided and the associated creep mechanism is well documented. [4,[7][8][9][10][11] Creep lifetime is one of the essential criteria to evaluate the creep performance, which is obtained by two traditional approaches.…”
Section: Introductionmentioning
confidence: 99%